Recurrence and propagation of past functions through mineral facilitated horizontal gene transfer - Verma, Taru; Hendiani, Saghar; Carbajo, Carlota; Andersen, Sandra B.; Hammarlund, Emma U.; Burmølle, Mette; Sand, Karina K. (Frontiers in Microbiology, 2024)
Horizontal gene transfer is one of the most important drivers of bacterial evolution. Transformation by uptake of extracellular DNA is traditionally not considered to be an effective mode of gene acquisition, simply because extracellular DNA is degraded in a matter of days when it is suspended in e.g. seawater. Recently the age span of stored DNA was increased to at least 2 Ma. We highlight that ancient environmental DNA can be fueling the evolution of contemporary bacteria. We show that Acinetobacter baylyi can incorporate 60 bp DNA fragments adsorbed to common sedimentary minerals and that the transformation frequencies scale with mineral surface properties. In contrast to heritable stochastic mutations, the processes by which bacteria acquire new genomic material at times with increased stress and needs, indicate a non-random mechanism that may propel evolution in a non-stochastic manner